Caracterização dos resíduos gerados em estação de tratamento de água de dupla filtração com o uso de polímeros - Silveira, Ana Christina Horner (Universidade Federal do Tocantins, 2016)
Water treatment plant residues requires special attention due its high potential os pollution and contamination if disposed in the natural environmental. The technology to treat the residues depends on technical and economic criteria, giving special attention on the quantitative and qualitative aspects of each alternative. This work focused on the treatment of residues produced in Double Filtration Water Treatment (Porto Nacional/TO, Brazil Plant), in order to study different types of synthetic polymers (cationic, anionic and nonionic) to both clarify in a jartest device and thick the sediment in Imhoff Cone. The results show that the cationic polymer was the most efficient in terms of the supernatant turbidity and the degree of thickening.